2008
DOI: 10.1159/000148250
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Epidermal Growth Factor Levels in Behçet’s Disease and Recurrent Aphthous Stomatitis

Abstract: Background: Epidermal growth factor (EGF) in saliva is cytoprotective against injuries and contributes to the maintenance of the integrity of the gastrointestinal mucosa. Low salivary EGF levels have been observed in patients with various forms of oral mucosal disease. Objective: Our aim wasto determine whether salivary EGF is low in patients with recurrent aphthous stomatitis (RAS) or those with Behçet’s disease (BD) when compared with healthy controls. Methods: The study population consisted of 33 BD and 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
(72 reference statements)
0
18
0
Order By: Relevance
“…In patients with radiation-induced oral mucositis, salivary EGF levels were significantly reduced and inversely correlated with the severity of the disease [14,15]. The authors of the above reports speculated that low salivary EGF levels reduce the capacity of the oral mucosa to heal and maintain its physiologic integrity, thereby increasing susceptibility to intraoral inflammatory lesions [4,[13][14][15]. In addition, the wound closure effect of EGF was shown in the previous study using oral epithelial cell lines [22].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In patients with radiation-induced oral mucositis, salivary EGF levels were significantly reduced and inversely correlated with the severity of the disease [14,15]. The authors of the above reports speculated that low salivary EGF levels reduce the capacity of the oral mucosa to heal and maintain its physiologic integrity, thereby increasing susceptibility to intraoral inflammatory lesions [4,[13][14][15]. In addition, the wound closure effect of EGF was shown in the previous study using oral epithelial cell lines [22].…”
Section: Discussionmentioning
confidence: 92%
“…Several previous reports suggested that EGF synthesized in the salivary glands and secreted into the saliva is involved in repair mechanisms that lead to wound healing and facilitate maintenance of the integrity of the oral cavity mucosa [10,11] and demonstrated the association between intraoral inflammatory diseases and changes in salivary EGF levels [4,[13][14][15]. Salivary EGF concentrations were found to be significantly lower in patients with stomatitis aphthosa [4,13] or peritonsillar abscess [4] and decreased further even after healing and in the absence of these lesions [4,13]. In patients with radiation-induced oral mucositis, salivary EGF levels were significantly reduced and inversely correlated with the severity of the disease [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is believed that the growth factors, which have a topical function, partly regulate the remission process. [1415]…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed Behcet's disease and RAS reduced the salivary EGF level even in the absence of oral ulcer. [15]…”
Section: Discussionmentioning
confidence: 99%